Perilaku Ibu Hamil dalam Mengkonsumsi Suplemen Mikronutrien - Shania Imelda; Restuning Widiasih; Raini Diah Susanti (Poltekkes Kemenkes Jakarta III, 2023)
ABSTRACT Micronutrient supplements are an important supplement for fetal growth and development. However, based on various studies, there are various factors that cause the lack of compliance of mothers in taking micronutrient supplements. The purpose of this study was to identify the behavior of pregnant women in taking micronutrient supplements. The design of this study used quantitative descriptive. The sample in this study was 327 pregnant women, from 3 health centers in Sumedang Regency. Sampling used cluster random sampling technique and sample size is calculated using Yamato's formula. The data of this study was obtained directly from respondents through filling out a structured questionnaire that was distributed using Google Form. The questionnaire contained compliance, frequency/dosage, and maternal habits in taking micronutrient supplements that had been tested for validity with 21 valid questions and a reliability test with Cronbach's Alpha a=0.94. Based on the results of the study, it showed that almost all respondents are pregnant women aged 20-35 years (87.1%). Most respondents behaved poorly in terms of compliance, frequency/dosage, and habits (52%) of taking micronutrient supplements. The conclusion of this study is that the behavior of pregnant women dominated by bad behavior, especially in taking vitamins A and B12. Advice for health workers is to collaborate in assisting the consumption of micronutrient supplements in pregnant women and to develop effective monitoring methods.